Item consistency in retrieving person-specific semantic information from faces and voices: An exploratory study in healthy subjects. Issue 4 (3rd July 2017) - Piccininni, Chiara; Gainotti, Guido; Trojano, Luigi; Luzzi, Simona; Papagno, Costanza; Carlesimo, Giovanni Augusto; Marra, Camillo; Quaranta, Davide
ABSTRACT: Controversies exist over the format of person-specific semantic representations in healthy subjects and the loss of part of these representations in conditions of brain pathology. Some authors have suggested that in brain-damaged patients item-specific consistency of errors through different recognition modalities might indicate a loss of person-specific information. This view is hindered by the fact that item consistency might also be variable in healthy subjects, because names, faces and voices have different degrees of effectiveness in the recognition of familiar people. The aim of the present research was to try to clarify this issue by assessing the value of consistency of semantic retrieval in a large sample of Italian healthy subjects who had judged as familiar the faces and voices of 40 Italian celebrities. The effect of fame level on item consistency was also evaluated. Results showed that the degree of item consistency between faces and voices was rather variable, for example it was influenced by fame level when the latter was based on an integrated (non-verbal) face/voice familiarity score, but not when it was based on the celebrities' names in a (verbal) questionnaire. The consistency between non-verbal assessment of fame and item consistency in retrieving information from faces and voices suggests a different specialization of the left anterior temporal lobe (ATL) for the verbally coded aspects of personal semantics and of the right ATL for the visual (face) and auditory (voice) aspects of person representation.